Increased efficacy of influenza virus vaccine candidate through display of recombinant neuraminidase on virus like particles - Guzman Ruiz, Leticia; Zollner, Alexander M.; Hoxie, Irene; Arcalis, Elsa; Krammer, Florian; Klausberger, Miriam; Jungbauer, Alois; Grabherr, Reingard (Frontiers in Immunology, 2024)
Vaccination against influenza virus can reduce the risk of influenza by 40% to 60%, they rely on the production of neutralizing antibodies specific to influenza hemagglutinin (HA) ignoring the neuraminidase (NA) as an important surface target. Vaccination with standardized NA concentration may offer broader and longer-lasting protection against influenza infection. In this regard, we aimed to compare the potency of a NA displayed on the surface of a VLP with a soluble NA. The baculovirus expression system (BEVS) and the novel virus-free Tnms42 insect cell line were used to express N2 NA on gag-based VLPs. To produce VLP immunogens with high levels of purity and concentration, a two-step chromatography purification process combined with ultracentrifugation was used. In a prime/boost vaccination scheme, mice vaccinated with 1 µg of the N2-VLPs were protected from mortality, while mice receiving the same dose of unadjuvanted NA in soluble form succumbed to the lethal infection. Moreover, NA inhibition assays and NA-ELISAs of pre-boost and pre-challenge sera confirm that the VLP preparation induced higher levels of NA-specific antibodies outperforming the soluble unadjuvanted NA.